Scaffolded programming projects to promote computational thinking - KOLESZAR, Victor; URRUTICOECHEA, Alar; OLIVERI, Andres; del Rosario SCHUNK, María; OYHENARD, Graciela (CTE-STEM 2022 conference, 2022)
In Uruguay, Plan Ceibal drives the complex task to impulse computational thinking in public schools. The CT framework used by the organization is to introduce computer science from primary and secondary education, with an approach focused on solving problems and coding as a language, and with the intention of taking advantage of the potential of computational thinking. In order to educate users and creators of technology. In 2021 the Computational Thinking program of Plan Ceibal impacted nearly 40 thousand students and teachers, this represents about 30% of the enrollment for K 4 to 6 courses (9 to 11 years old) of the public elementary school. This study explored the impact of the implementation of scaffolded programming projects and final evaluation, in a subset of elementary schools groups. Preliminary results suggest a good adoption of the program and high participation of students and teachers registered through the learning management system (LMS) platform. In addition, the students who had more active participation in the classes had significantly higher performances in the programming tests. Some differences were observed in favor of girls. Results are discussed in relation to the pedagogical characteristics of the program.